Effect of water saving micro-irrigation techniques on growth and yield of wheat in North West India - SURYAVANSHI, PRIYANKA; BUTTAR, GURMEET SINGH (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted during rabi 2013-14 and 2014-15 on wheat at research farm of Punjab Agricultural University, Ludhiana, India. The study aimed to evaluate effect of three different irrigation methods (check basin, drip and sprinkler irrigation) and four irrigation regimes (Cumulative pan evaporation: irrigation water) CPE/IW ratio of 0.6, 0.8, 1.0 and 1.2 with inclusion of recommended surface irrigation (7.5 cm depth) as standard check on plant growth parameters and yield of wheat. Results revealed that drip irrigation improved leaf area index, dry matter accumulation, yield attributes and grain yield. Among the irrigation schedules all growth and yield parameters increased markedly with increase in irrigation regimes from CPE: IW 1.2 to 0.6, suggesting the need for adopting micro irrigation systems for wheat in this region.